Liquidity and Financial Resilience: Lessons from Indonesia Amid COVID-19 Resurgence - Irianto, Ellen D. Oktanti; Kesuma, Muhammad Ramadhani; Henrika, Margareth; Widaryo, Chandika Mahendra; Aini, Rohana Nur; Ariswati, Lusiana Desy (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The resurgence of COVID-19 in Indonesia highlights the critical need for effective financial strategies in vulnerable sectors. This study explores the influence of liquidity management practices, specifically cash, current, and quick ratios, on financial resilience, measured by debt-to-equity ratio and return on assets, in Indonesia’s retail and tourism sectors during the pandemic period. Utilizing panel regression analysis with data from publicly listed firms, the research incorporates firm size as a control variable. Findings indicate that liquidity management has a limited impact on financial resilience, with firm size and digital transformation playing more significant roles. Government interventions and sub-sectoral differences further shape financial outcomes, offering critical insights for navigating future crises. The study contributes to understanding financial strategies in emerging markets, providing actionable recommendations for businesses and policymakers to enhance resilience amid ongoing pandemic uncertainties in Indonesia and ASEAN. By addressing sectoral dynamics, this research underscores the importance of adaptive strategies in ensuring economic stability.